2019
DOI: 10.1148/radiol.2018181485
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Mass-forming Cholangiocarcinoma: Arterial Enhancement Patterns at MRI and Prognosis

Abstract: To identify whether arterial enhancement pattern at MRI could predict the prognosis after surgical resection of intrahepatic mass-forming cholangiocarcinoma (IMCC). Materials and Methods: Patients who underwent curative hepatic resection and preoperative MRI for IMCC from November 2007 to September 2016 were retrospectively evaluated. MRI enhancement pattern was classified by two radiologists. Recurrence and death data were retrieved until September 31, 2017. Prognostic factor analysis was performed by using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 28 publications
(47 reference statements)
5
68
0
Order By: Relevance
“…Favorable microvascular and macrovascular conduit in this study were associated with the best outcomes. In a retrospective study of patients with iCCA treated with resection, the 5-year risk of death in patients with diffuse tumor hyperenhancement per preoperative magnetic resonance imaging was lower when compared to tumors with either peripheral enhancement or diffuse hypoenhancement (5-year risk of death: 5.9% vs 59.2% vs 87.9%) [ 8 ]. Our study similarly identified hypoenhancement (unfavorable microvascular conduit) as a negative marker for survival with HR 5.7 (95% CI 1.1–28.9, p = 0.034).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable microvascular and macrovascular conduit in this study were associated with the best outcomes. In a retrospective study of patients with iCCA treated with resection, the 5-year risk of death in patients with diffuse tumor hyperenhancement per preoperative magnetic resonance imaging was lower when compared to tumors with either peripheral enhancement or diffuse hypoenhancement (5-year risk of death: 5.9% vs 59.2% vs 87.9%) [ 8 ]. Our study similarly identified hypoenhancement (unfavorable microvascular conduit) as a negative marker for survival with HR 5.7 (95% CI 1.1–28.9, p = 0.034).…”
Section: Discussionmentioning
confidence: 99%
“…Whether a similar dose relationship is present with cholangiocarcinoma remains unknown. Additionally, unresectable iCCA also presents with blood supply variation and anatomic complexity, which may affect outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiologically, hypervascular iCCAs harbour more favourable outcomes and a less aggressive nature than those with hypovascular features. [26][27][28] Hypervascular iCCAs are also associated with high microvascular density (MVD), arterial vessel density (AVD) and CLC subtype on histopathology. 26,27,[29][30][31] However, the vasculature of each iCCA histological subtype, reflecting divergences in blood imaging, remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Mass-forming intrahepatic cholangiocarcinoma (ICC), the most common subtype of ICC (followed by periductal infiltrating and intraductal growth subtypes), is an epithelial malignancy of the intrahepatic bile ducts that is typically associated with poor patient outcomes; as less than 40% of patients with resectable ICC survive more than 5 years, and those with unresectable disease typically survive less than 12 months [1][2][3][4]. Although the incidence of ICC is highest in Asia, a rise in known risk factors (such as chronic viral hepatitis, cirrhosis, primary sclerosing cholangitis, fibropolycystic liver disease, and recurrent pyogenic cholangitis) has led to a worldwide rise in its incidence and mortality over the past two decades [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%